The Development of E-Book-Based Teaching Materials Through a Culturally Responsive Teaching Approach in Elementary Schools - Pratiwi, Desi Eka; Yuliana, Leni; Partika, Neta Tabhita; Noorwinanda, Muhammad Navis Roihan Daru (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The aim of this research is to develop e-book-based teaching materials through the Culturally Responsive Teaching (CRT) approach that are engaging and aligned with the characteristics of elementary school students. This research is developmental research using the ADDIE model, which consists of five steps: Analyze, Design, Develop, Implementation, and Evaluation. Data collection techniques include interviews, questionnaires, and validation sheets. The researcher involved two validators to validate the e-book and one validator to validate the content within the e-book. Based on the validation results, it was found that: (1) The e-book-based teaching materials developed by the researcher are categorized as valid/feasible with a percentage of 91.25%. (2) The content within the e-book is proven to be effective and suitable for the characteristics of elementary school students, with a percentage of 85%, categorized as valid/feasible. (3) The student response questionnaire indicated that the use of the e-book is effective and easy to understand, with a percentage of 91.53%, categorized as excellent. Based on the data analysis results, it can be concluded that the development of e-book-based teaching materials through the Culturally Responsive Teaching approach is valid/feasible for use in 5th-grade Indonesian language lessons on Compound Sentences. Keywords: Teaching Materials; E-book; Culturally Responsive Teaching Approach; Elementary School